Teachers Self-regulation in Solving the Problem with Contradiction Information - Sri Indriati Hasanah; Hasan Basri; Ukhti Raudhatul jannah; Evha Nazalatus Sa’adiyah Sy; Harfin Lanya (Didaktik Matematika, 2022)
The teacher's self-regulation in solving problems with contradictory information needs to be investigated because this certainly has an impact on students' self-regulation abilities. However, research related to this is still limited. Problem with Contradiction Information (PWCI) is appropriate to view self-regulation. This research is a case study which involved teachers in East Java, Indonesia and already have an educator certificate. There are 24 teachers as participants of this research, 14 females and 10 males. The objectives of this study describe how the teacher's response when completing PWCI and how the teacher's self-regulation when solving PWCI. Data were collected through tests and interviews. The results show that (1) There are two types of teacher responses in completing PWCI, the first type is the teacher who answers the questions directly without checking the provided information, the second type is the teacher who is thorough and cross-checks before working on the questions, (2) The emergence of self-assessment teacher regulation when completing PWCI is divided into four, namely, teacher self-regulation appears at the stage of understanding, implementing, re-checking and does not appear when completing PWCI. Most of the teachers are not aware of the contradictions in the questions given.